2002
DOI: 10.1177/088506660201700203
|View full text |Cite
|
Sign up to set email alerts
|

Medical Disorders Related to Diving

Abstract: Exposure to the underwater environment is associated with several unique disorders that may require recompression in a hyperbaric chamber. Increasing pressure during descent reduces the volume of the paranasal sinuses and middle ear, which, if not properly equalized, will sustain injury due to barotrauma. Barotrauma of the inner ear results in vertigo, tinnitus, and often permanent hearing loss. During ascent, expanding gas can produce lung injury accompanied by pneumothorax, mediastinal and subcutaneous emphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
0
11
0
1
Order By: Relevance
“…In recent years, the number of scuba divers has been growing 1) . However, scuba diving may trigger problems in some parts of the body such as the nose, ear, lung, and temporomandibular joint [2][3][4][5][6] . Previous studies reported that the prevalence of temporomandibular disorders while scuba diving ranged from 24% to 68% [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the number of scuba divers has been growing 1) . However, scuba diving may trigger problems in some parts of the body such as the nose, ear, lung, and temporomandibular joint [2][3][4][5][6] . Previous studies reported that the prevalence of temporomandibular disorders while scuba diving ranged from 24% to 68% [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of decompression illness is made on clinical grounds since gas bubbles are rarely detectable on imaging [ 1 ]. The most common symptoms of decompression sickness are localized pain, numbness/paresthesia and muscular weakness, typically presenting within the first 24 h, whereas symptoms of air embolism from pulmonary barotrauma occur immediately upon ascent [ 4 , 5 ]. Although no diagnostic blood test exists for air embolism, widespread air embolization has been reported to result in elevated serum creatine kinase of up to 900 U/L [ 6 ], as was the case in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…The most common clinical manifestations result from gas emboli to the brain which can occur on ascent and produce syncope. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%